Xanthoria parietina as a biomonitor of airborne heavy metal pollution in forest sites in the North East of Morocco - El Rhzaoui, Ghita; Divakar, Pradeep K.; Crespo, Ana; Tahiri, Hikmat; El Alaoui-Faris, Fatima Ezzahra (Lazaroa, 2015)
Xanthoria parietina, common foliose lichen, growing in its natural habitat, was analysed for the concentration of five heavy metals (Fe, Cr, Zn, Pb and Cu) from different forest sites of North East of Morocco (Kenitra, Sidi Boughaba, Mkhinza, Ceinture Verte near Temara city, Skhirate, Bouznika and Mohammedia). The quantification was carried out by inductively coupled plasma - atomic emission spectrometry (ICP-AES). Results were highly significant p
Keywords: Biomonitoring; air contamination; inductively coupled plasma - atomic emission spectrometry; Scanning Electron Microscopy